1 Corinthians: a commentary - Ellis, Edward Earle (Bloomsbury Publishing Plc, 2022)
Cover -- Title -- Copyright -- Dedication -- Contents -- Preface -- I Address and Salutation (1:1-3) -- II Thanksgiving (1:4-9) -- III True and False Wisdom (1:10-4:21) -- IV Sexual Relationships: Immoral and Moral (5:1-7:40) -- V Liberty's Boundaries: Re Idol Food (8:1-11:1) -- VI The Regulation of Church Services (11:2-14:40) -- Epilogue -- Index.